Competitive ability of soybean cultivars with horseweed (Conyza bonariensis) - Trezzi,M.M. (2013)
The existence of large areas infested with populations of Conyza spp. resistant to glyphosate in Brazil demands appropriate and integrated management strategies. This experiment aimed to identify soybean cultivars with greater competitive ability with horseweed plants and to determine plant characteristics associated with this ability. The experiment was arranged in a randomized complete block design with split plots. Seven soybean cultivars (CD 225 RR, BRS 232, CD 226 RR, NK 7054 RR, BMX Apollo RR, BRS 245 RR and BRS 255 RR) were allocated in the plots, and two interference situations (absence and 13.3 plants of Conyza m-2, transplanted seven days before soybean planting) in the subplots. The average yield loss due to competition with horseweed was 25%. Cultivar CD 226 RR showed no significant grain yield loss due to competition, compared to the control without infestation, but showed the lowest average grain yield. The BRS 232 genotype showed loss of grain yield of only 14%, and presented positive plant height and leaf mass at 20 DAE, as well as dry matter of stems+branches in all evaluations, features related to its higher performance and greater ability to withstand competition with horseweed plants.